What is history for? - Southgate, Beverley C. (London Routledge, 2005)
"What is History For? is a timely publication that examines the purpose and point of historical studies. Charting the development of historical studies, Beverley Southgate examines the various uses to which history has been put. While history has often supposedly been studied 'for its own sake', Southgate argues that this seemingly innocent approach masks an inherent conservatism and exposes the ways in which history has, sometimes deliberately, sometimes inadvertently, been used for socio-political purposes. With traditional notions of truth and historical representation now under question, it has become vital to rethink the function of history and renegotiate its uses for the postmodern age. History in the 21st century, Southgate proposes, should adopt a morally therapeutic role that seeks to advance human hope and happiness."--BOOK JACKET.
Humanities and therapeutic education -- History for its own sake -- The Holy Grail of truth -- 'For its own sake'? -- Straw men? -- Professed purposes -- Transferable skills -- 'Cultivation' -- Myth-breaking -- Theological confirmations and questionings -- Obligations to the dead -- Hidden agendas -- Political puppertry: the case of Germany -- Justifying the status quo -- Discipline and power -- The gender of history -- Life and needs in postmodernity -- Postmodernity -- Centres and certainties -- Order -- Direction -- Problems of identity: selfhood and others -- History in postmodernity: future prospects -- Closure and openness -- Self, narrativity and meaning: personal and national identities -- Historic moments and empowerment: making choices -- Colonising the future: towards a better world -- Histories for postmodernity -- some aspirations -- Realism, pessimism, hope -- History and myth again -- The labyrinth of language -- Transferable qualities -- Histories for postmodernity -- some examples -- Robert A. Rosenstone and Japan -- Peter Novick and the Holocaust -- Sven Lindqvist and bombing -- Tzvetan Todorov and hope.
Includes bibliographical references (p. [184]-208) and index.
Keywords: History -- Philosophy